Boundary Value Analysis Testing Techniques on Learning Management System Applications - Prayudha, I Putu Astya; Hartani, Rukmi Sari; Divayana, Yoga (International Journal of Engineering and Emerging Technology; Vol 4 No 2 (2019): July - December, 2020)
Application of Learning Management System of Lampung State Polytechnic (LMS Polinela) is an elearning application developed as an alternative teaching media that aims to complement existing teaching media to help students learn independently so that learning outcomes are more optimal and efficient. This study uses a black box testing boundary value analysis technique in testing the Polinela LMS application. This boundary value analysis technique works by determining the upper and lower limits of the data to be tested, after which the data is inputted to the Polinela LMS application. The results of the review of the journal from Zuriati et al with the title "Testing Technique of Boundary Value Analysis in the Polinela Learning Management System Application" is to provide a clear understanding of the theory of Boundary Value Analysis. The Boundary Value Analysis technique described has been able to provide a description of the stages and processes in testing each functionality. The process functionality is explained thoroughly so that the reader can better understand and know the entire process that is in the application. Index Terms— Learning management system, black box, boundary value analysis